Peningkatan Kemampuan Kognitif Melalui Media Game Interaktif Wordwall Pada Kelompok B di Permata Hati Islamic Preschool - Almiatullah, Almiatullah; Gunawan, Gunawan; Astini, Baik Nilawati; Rachmayani, Ika (Indonesian Publication Center, 2025)
This study aimed to measure the improvement of cognitive abilities in Group B children at Permata Hati Islamic Preschool through the use of Wordwall interactive game media. The research employed a Classroom Action Research (CAR) design, utilizing Kurt Lewin's model, and was conducted in two cycles. The study's population comprised Group B children, with the sample consisting of 13 students from the Ali Bin Abi Thalib class (6 girls and 7 boys). Data collection techniques included observation and tests. The findings revealed a significant increase in students' cognitive abilities. In the pre-cycle stage, 30.76% of students demonstrated achieved cognitive abilities, which rose to 69.23% in Cycle I and further to 84.61% in Cycle II. This indicates an improvement in children's cognitive abilities by 38.47% from the pre-cycle to Cycle I, and 15.38% from Cycle I to Cycle II. Furthermore, test results also showed a substantial increase, from 61.53% in Cycle I to 100.00% in Cycle II. Therefore, the use of Wordwall interactive game media proved effective in enhancing children's cognitive abilities, particularly in Group B.